A field guide to plants of Costa Rica - Gargiullo, Margaret B., 1942-2019 (Oxford University Press, 2008)
At the biological crossroads of the Americas, Costa Rica hosts one of the widest varieties of plants in the wold, with habitats ranging from tidal mangrove swamps, and lowland rainforests, to dry tropical evergreen and deciduous forests. Field Guide to Plants of Costa Rica is a must-have reference guide for beginner and expert naturalists alike. It provides a thorough survey of more than 850 plant species, each entry accompanied by color photos and a concise yet detailed narrative description. Plants are conveniently grouped by the different types of vegetation: palms, tall trees, shrubs, wood.